Vaksin malaria dan perkembangannya - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRACT Malaria vaccine development is advancing rapidly competing with drug development. New findings in vaccine research almost create a wider gap from success due to variation and diversity of the antigen (epitope). On evolutionary grounds, P. fakiparum is the most likely to have untapped adaptive potential when it is put under effective immune pressure. The changes may ercten d to the circumsporozoite (CS) protein. Later it was found that the sequence of NANP in the CS gene predominates with minor repeats of NVDP. This trimer (NANP) formation repeated 37 times in Brazilian clones and 43 times in Wellcome strain. There are regions of very high structural homolgy in all CS protein. These conserved regions I and A that may subserve a common function, may be related to cell invasion. Region I is immediately aminoterminal to the repeats, and region 11 is homologous to human thrombospondin. Antibody raised against peptides from region I blocked merozoite invasion in the liver in vitro.